Brand equity in the Portuguese vinho verde “green wine” market - Brochado, A.; Oliveira, F. (International Journal of Wine Business Research, 2018)
Purpose This paper aims to examine the main determinants of brand equity in the context of brands defined by their region of origin, as is the case for Portuguese green wine. Design/methodology/approach Data were collected from a sample of wine consumers in Portugal through personal interviews (N = 200). Structural equation modelling was then applied to study the causal relationships between brand equity and its dimensions (i.e. brand loyalty, brand awareness, perceived quality and brand association) for top-of-mind green wine brands, based on Aaker’s conceptual Framework (Aaker, 1991). Findings The study’s results reveal that brand loyalty is the most influential dimension of brand equity for Portuguese green wine and that the links between brand equity and both brand association and perceived quality are significant. These findings can help Portuguese wineries to prioritise – and allocate resources across – brand equity dimensions. Originality/value Although the literature identifies dimensions of brand equity in other industries, the literature on the wine market is still sparse. This study, therefore, contributes to expanding this body of knowledge.